Islamophobia and Allegations Against Corona Virus Spread By Muslim Minority In India - Muhammad Saekul Mujahidin (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This article discusses Islamophobia and accusations by the Hindu majority against Muslim minorities in India against the coronavirus. The Bharatiya Janata Party (BJP) is one of the parties that often voices accusations against Muslim minorities in India for this incident. The Tablighi Jamaat in New Delhi is one of the targets and accusations of the Hindu majority against Muslims in India. The purpose of this study is to find out the reasons why Hindus accuse Muslims in India of being the cause of the spread of the coronavirus